Pengembangan Gelling Agent dan Uji Evaluasi Fisik Sediaan Facial Wash Gel Berbasis Umbi dan Kulit Singkong (Manihot Esculenta) - Eka Safitri; Tutik Tutik; Angga Saputra Yasir (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Facial wash gel is a gel-based facial cleanser widely used because it is easy to apply and provides comfort to the skin. This preparation requires a gelling agent to form a gel structure, so alternative natural ingredients from cassava tubers and peels (Manihot esculenta) were used. This study aimed to determine the ability of cassava tubers and peels as gelling agents in facial wash gel formulations and to evaluate the physical characteristics of the resulting preparation. The research method involved making flour and starch from cassava tubers and peels, then formulating them into facial wash gel preparations and conducting physical evaluation tests. The organoleptic test results showed that F1–F4 were in the form of thick sediment and F5 was in the form of a gel with a brown and white color and a distinctive soapy smell. The pH test results showed values ranging from 7.6–8.7 with significant differences between formulas. The foam height test results showed values of 2.0–2.4 and did not differ significantly between formulas. The homogeneity test results showed that only F5 was homogeneous, while F1–F4 were not homogeneous. The cleaning power test results showed that all formulations were able to reduce stains, with F3 having the highest cleaning power value. The conclusion of this study shows that cassava tubers and skin (Manihot esculenta) can be formulated as a facial wash gel, but it has not formed an optimal gel due to insufficient concentration, even though it has met the cleaning power capability.